2021
DOI: 10.1371/journal.pmed.1003735
|View full text |Cite|
|
Sign up to set email alerts
|

Accuracy of novel antigen rapid diagnostics for SARS-CoV-2: A living systematic review and meta-analysis

Abstract: Background SARS-CoV-2 antigen rapid diagnostic tests (Ag-RDTs) are increasingly being integrated in testing strategies around the world. Studies of the Ag-RDTs have shown variable performance. In this systematic review and meta-analysis, we assessed the clinical accuracy (sensitivity and specificity) of commercially available Ag-RDTs. Methods and findings We registered the review on PROSPERO (registration number: CRD42020225140). We systematically searched multiple databases (PubMed, Web of Science Core Coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
273
4
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(313 citation statements)
references
References 281 publications
28
273
4
8
Order By: Relevance
“…In addition, our meta-analysis revealed that antigen test sensitivity [96.0% (95% CI: 90.0, 99.0)] was highest in SARS-CoV-2-positive individuals with an increased likelihood of being infectious at the time of testing (e.g., culture positive; Pekosz et al, 2021). Although specificity data were not extracted for every study included in this meta-analysis, SARS-CoV-2 antigen testing had high specificity as published previously (Brümmer et al, 2021). Experimental factors such as anatomical collection site, specimen storage conditions, analytical sensitivity of reference, and composition of the study population with respect to symptomology all varied across the field of studies included here.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In addition, our meta-analysis revealed that antigen test sensitivity [96.0% (95% CI: 90.0, 99.0)] was highest in SARS-CoV-2-positive individuals with an increased likelihood of being infectious at the time of testing (e.g., culture positive; Pekosz et al, 2021). Although specificity data were not extracted for every study included in this meta-analysis, SARS-CoV-2 antigen testing had high specificity as published previously (Brümmer et al, 2021). Experimental factors such as anatomical collection site, specimen storage conditions, analytical sensitivity of reference, and composition of the study population with respect to symptomology all varied across the field of studies included here.…”
Section: Discussionmentioning
confidence: 73%
“…As others have noted previously, a wide range of reported sensitivities has been documented for rapid antigen testing (Dinnes et al, 2020;Brümmer et al, 2021). The main objective of this meta-analysis was to explore possible causes of the high degree of heterogeneity of assay sensitivity estimates across different studies.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations